Incidence of Symptomatic Vertebral Fractures Among Newly Diagnosed Autoimmune Diseases Initiating Glucocorticoid Therapy - Migita, Kiyoshi (Medicine (Baltimore), 2015)
Few data are available regarding vertebral fracture risk in patients treated with corticosteroids including patients with interstitial lung disease (ILD). The aim of the present study was to identify risk factors for symptomatic vertebral fracture analyzed in patients with newly diagnosed autoimmune diseases. This was an observational cohort study conducted in the National Hospital Organization-EBM study group from 2006 to 2008. The study subjects were autoimmune disease patients who were newly treated with glucocorticoids (GCs). The primary endpoint was the first occurrence of vertebral fracture diagnosed by x-rays. Cox proportional-hazards regression was used to determine independent risk factors for vertebral fracture with covariates including sex, age, comorbidity, laboratory data, use of immunosuppressants, and dose of GCs. Survival was analyzed according to the Kaplan–Meier method and assessed by the log-rank test. Among 604 patients of mean age 59.5 years and mean GC dose 50.4 mg/d (first 1 months), 19 patient (3.1%) had at least 1 symptomatic vertebral fracture during 1.9 years of follow-up period. Cox regression model demonstrated that the relative risk for symptomatic vertebral fracture was independently higher in patient with ILD (hazard ratio [HR] = 2.86, 95% confidence interval [CI] = 1.10–7.42, P = 0.031) and in every 10-year increment of the age of disease onset (HR = 1.57, 95% CI = 1.09–2.26, P = 0.015). Kaplan–Meier analyses demonstrated that the incidence of vertebral fractures in patients with ILD was significantly higher in comparison with those without ILD. Our results indicate a higher risk of vertebral facture in patients with ILD and elderly patients during the initial GC treatment against autoimmune diseases. There is a need for further, even longer-term, prospective studies subjected patients with autoimmune disease, including ILD, under GC treatment.